2023
DOI: 10.1177/00846724231190958
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive literature review of Islam-oriented scales on religiosity, spirituality, and morality

Urfath Nabi,
Shawkat Ahmad Shah,
Adil Hussain Seh

Abstract: Measurements play a significant role in the scientific investigation of religious phenomena. The study of religion, in general, has attracted considerable attention from academia and literature. The aim of this study was to conduct a systematic analysis of the literature regarding scales that have been developed for measuring variables with Islamic relevance and importance, having a theoretical framework embedded in the primary sources of Islamic literature (the Quran and hadith) and validated on Muslim sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…There were several factors that influenced the decision to conduct this study. To begin with, a thorough examination of Islamic-oriented scales, such as that undertaken by Salleh et al (2016), Aziz et al (2021), andNabi et al (2023), showed that the most measured components related to Islam are personality, religiosity, beliefs, and morality, which include repentance, This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Research Motivation/rationale For the Studymentioning
confidence: 99%
See 4 more Smart Citations
“…There were several factors that influenced the decision to conduct this study. To begin with, a thorough examination of Islamic-oriented scales, such as that undertaken by Salleh et al (2016), Aziz et al (2021), andNabi et al (2023), showed that the most measured components related to Islam are personality, religiosity, beliefs, and morality, which include repentance, This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Research Motivation/rationale For the Studymentioning
confidence: 99%
“…fear, hope, gratitude, and so forth, falling under four categories: religiosity, spirituality, morality, and Islamic well-being (Nabi et al, 2023). The majority of the scales measures religiosity (Nabi et al, 2023).…”
Section: Akhla ¯Q Toward Othersmentioning
confidence: 99%
See 3 more Smart Citations